UPAYA MENGATASI KETERGANTUNGAN SISWA TERHADAP CHATGPT DALAM PEMBELAJARAN CERPEN KELAS XI DI SMA DENGAN MENGGUNAKAN METODE PEER REVIEW DISCUSSION - Elmirna, Nora; Sujinah, Sujinah (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
ABSTRACT The development of artificial intelligence, particularly ChatGPT, has provided convenience in writing instruction; however, its uncontrolled use has the potential to create dependency and reduce students’ creativity. This study aims to reduce students’ reliance on ChatGPT in short story writing instruction through the implementation of the Peer Review Discussion method among eleventh-grade students at SMA Negeri 02 Bombana. The study employed a Classroom Action Research design based on the Kemmis and McTaggart model, conducted in two cycles. In Cycle I, students were still allowed to use ChatGPT as a stimulus for generating initial ideas, whereas in Cycle II the use of ChatGPT was completely eliminated to encourage independent thinking. The findings indicate that in Cycle I, students’ short stories were still dominated by uniform language patterns and low levels of originality, and participation in peer review activities had not yet been optimal. In Cycle II, the strengthened implementation of Peer Review Discussion increased students’ active engagement in providing feedback, deepened their understanding of the intrinsic elements of short stories, and resulted in more varied and original written works. Overall, the quality of students’ short stories improved, and their dependence on ChatGPT decreased significantly. Thus, the Peer Review Discussion method proved effective in enhancing students’ creativity, independence, and short story writing skills amid the challenges posed by the use of AI technology in education. Perkembangan kecerdasan buatan, khususnya ChatGPT, memberikan kemudahan dalam pembelajaran menulis, namun penggunaannya yang tidak terkontrol berpotensi menimbulkan ketergantungan dan menurunkan kreativitas siswa. Penelitian ini bertujuan untuk mengurangi ketergantungan siswa terhadap ChatGPT dalam pembelajaran menulis cerpen melalui penerapan metode Peer Review Discussion pada siswa kelas XI SMA Negeri 02 Bombana. Penelitian menggunakan desain Penelitian Tindakan Kelas model Kemmis dan McTaggart yang dilaksanakan dalam dua siklus. Pada siklus I, siswa masih diperkenankan memanfaatkan ChatGPT sebagai pemicu ide awal, sedangkan pada siklus II penggunaan ChatGPT ditiadakan sepenuhnya untuk mendorong kemandirian berpikir. Hasil penelitian menunjukkan bahwa pada siklus I cerpen siswa masih didominasi pola bahasa yang seragam dan tingkat orisinalitas yang rendah, serta partisipasi dalam kegiatan peer review belum optimal. Pada siklus II, penguatan Peer Review Discussion mampu meningkatkan keaktifan siswa dalam memberikan umpan balik, memperdalam pemahaman unsur intrinsik cerpen, serta menghasilkan karya yang lebih variatif dan orisinal. Secara keseluruhan, kualitas cerpen siswa meningkat dan ketergantungan terhadap ChatGPT menurun secara signifikan. Dengan demikian, metode Peer Review Discussion terbukti efektif dalam meningkatkan kreativitas, kemandirian, dan kemampuan menulis cerpen siswa di tengah tantangan penggunaan teknologi AI dalam pembelajaran.